2008
DOI: 10.1186/1744-8069-4-61
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TRPV1 in Different Subtypes of Dorsal Root Ganglion Neurons in Rat Chronic Inflammatory Nociception Induced by Complete Freund's Adjuvant

Abstract: Background: The present study aims to investigate the role of transient receptor potential vanilloid 1 (TRPV1) in dorsal root ganglion (DRG) neurons in chronic pain including thermal hyperalgesia and mechanical allodynia. Chronic inflammatory nociception of rats was produced by intraplantar injection of complete Freund's adjuvant (CFA) and data was collected until day 28 following injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 27 publications
9
124
0
Order By: Relevance
“…S7 A and B). These observations corroborate other studies that use the same doses of these antagonists in different rodent models of inflammatory pain (14,29,30). Similarly, IT HXA 3 -induced tactile allodynia is significantly attenuated by spinal pretreatment with antihyperalgesic doses of HC030031 or AMG9810 (Fig.…”
Section: Hxa 3 Activates Trpv1 and Trpa1 On Sensory Neurons And Triggerssupporting
confidence: 90%
“…S7 A and B). These observations corroborate other studies that use the same doses of these antagonists in different rodent models of inflammatory pain (14,29,30). Similarly, IT HXA 3 -induced tactile allodynia is significantly attenuated by spinal pretreatment with antihyperalgesic doses of HC030031 or AMG9810 (Fig.…”
Section: Hxa 3 Activates Trpv1 and Trpa1 On Sensory Neurons And Triggerssupporting
confidence: 90%
“…DomBourian et al (2006) showed that there was an upregulation of TRPV1 in the DH of rats after spinal cord injury, and Tohda et al (2001) demonstrated that carrageenan-induced inflammation resulted in an increased transport of TRPV1 mRNA to neuron terminals in the DH. Both models were associated with thermal hyperalgesia, which has been shown to be blocked by intrathecal administration of TRPV1 antagonists such as 3,6-dihydro-3Ј- (Wang and Woolf, 2005;Cui et al, 2006;Yu et al, 2008). Studies have also shown that spinal TRPV1 is likely to be involved in the development of mechanical hyperalgesia (Kanai et al, 2007).…”
Section: E In the Spinal Cordmentioning
confidence: 99%
“…The rats were briefly anesthetized with 3% isoflurane, flexed over a tube, and a 27-gauge needle was inserted between the L5 and S1 vertebrae with a deflection of the tail indicating entry to the subarachnoid space. The dose of both agents were chosen based on previously published studies (Yu et al, 2008;Li et al, 2014b). AMG9810 was tested on both preestablished paclitaxel CIPN and as a preventative agent during chemotherapy.…”
Section: Methodsmentioning
confidence: 99%